Prospective cohort study: Causes of stillbirth in Australia 2013–2018. (19th April 2021) - Sexton, Jessica K.; Mahomed, Kassam; Marsden, Tania; Coory, Michael; Gardener, Glenn; Ellwood, David; Gordon, Adrienne; Shand, Antonia W.; Yee Khong, Teck; Gordon, Louisa G.; Flenady, Vicki
Abstract : Background: Stillbirth is a major public health problem that is slow to improve in Australia. Understanding the causes of stillbirth through appropriate investigation is the cornerstone of prevention and important for parents to understand why their baby died. Aim: The aim of this study is to assess compliance with the Perinatal Society of Australia and New Zealand (PSANZ) Perinatal Mortality Clinical Practice Guidelines (2009) for stillbirths. Methods: This is a prospective multi‐centred cohort study of stillbirths at participating hospitals (2013–2018). Data were recorded into a purpose‐built database. The frequency of the recommended core investigations was calculated, and χ 2 test was performed for subgroup analyses by gestational age groups and timing of fetal death. A 70% compliance threshold was defined for investigations. The cause of death categories was provided according to PSANZ Perinatal Death Classification. Results: Among 697 reported total stillbirths, 562 (81%) were antepartum, and 101 (15%) were intrapartum. The most common cause of death categories were 'congenital abnormality' (12.5%), 'specific perinatal conditions' (12.2%) and 'unexplained antepartum death' (29%). According to 2009 guidelines, there were no stillbirths where all recommended investigations were performed (including or excluding autopsy). A compliance of 70% was observed for comprehensive history (82%), full blood count (94%), cytomegalovirus (71%), toxoplasmosis (70%), renal function (75%), liver function (79%), external examination (86%), post‐mortem examination (84%) and placental histopathology (92%). The overall autopsy rate was 52%. Conclusions: Compliance with recommended investigations for stillbirth was suboptimal, and many stillbirths remain unexplained. Education on the value of investigations for stillbirth is needed. Future studies should focus on understanding the yield and value of investigations and service delivery gaps that impact compliance.